TECHNOLOGIES FOR IMPROVING THE EFFICIENCY OF FUEL SUPPLY SYSTEMS IN GAS-FUELED VEHICLES - Pardayev Rustam Kamol o‘g‘li (Web of Journals Publishing, 2025)
This scientific article examines the technologies for improving the efficiency of fuel supply systems in gas-fueled vehicles. The study demonstrates that using compressed natural gas (CNG) and liquefied petroleum gas (LPG) not only reduces harmful emissions such as CO₂ and NOx by 20–35%, but also increases fuel efficiency, prolongs engine and mechanical component life, and lowers operational costs. Key technologies discussed include automatic fuel injector systems, digital monitoring and diagnostics, high-efficiency engine designs, and optimized fuel supply systems. The research concludes that a comprehensive approach combining these technologies ensures environmental safety, economic efficiency, and technical reliability of gas-fueled vehicles. The results have practical relevance for vehicle manufacturers, transport companies, and fuel system developers aiming to implement environmentally friendly and efficient transportation solutions.
Keywords: gas-fueled vehicles, fuel supply system, efficiency improvement, automatic injector, digital monitoring, environmental safety.